Water relations and hydraulic architecture in Cerrado trees: adjustments to seasonal changes in water availability and evaporative demand - Bucci, Sandra Janet (2008)
We determined adjustments in physiology and morphology that allow Neotropical savanna trees from central Brazil (Cerrado) to avoid water deficits and to maintain a nearly constant internal water balance despite seasonal changes in precipitation and air saturation deficit (D). Precipitation in the study area is highly seasonal with about five nearly rainless months during which D is two fold higher compared to wet season values. As a consequence of the seasonal fluctuations in rainfall and D, soil water potential changes substantially in the upper 100 cm of soil, but remains nearly constant below 2 m depth. Hydraulic architecture and water relations traits of Cerrado trees adjusted during the dry season to prevent increasing water deficits and insure homeostasis in minimum leaf water potential ΨL and in total daily water loss per plant (isohydry). The isohydric behavior of Cerrado trees was the result of a decrease in total leaf surface area per tree, a strong stomatal control of evaporative losses, an increase in leaf-specific hydraulic conductivity and leaf hydraulic conductance and an increase in the amount of water withdrawn from internal stem storage, during the dry season. Water transport efficiency increased in the same proportion in leaves and terminal stems during the dry season. All of these seasonal adjustments were important for maintaining ΨL above critical thresholds, which reduces the rate of embolism formation in stems and help to avoid turgor loss in leaf tissues still during the dry season. These adjustments allow the stems of most Cerrado woody species to operate far from the point of catastrophic dysfunction for cavitation, while leaves operate close to it and experience embolism on a daily basis, especially during the dry season.